Behavioral analysis of learning and memory in Anastrepha fraterculus. Issue 2 (10th January 2015) - Gregório, Patrícia L.F.; Sant'Ana, Josué; Pires, Patrícia D.
Abstract We evaluate the influence of prior exposure to artificial substrate for oviposition on learning and memory in the fruit fly Anastrepha fraterculus (Wiedemann) (Diptera: Tephritidae). Some females were previously exposed to artificial fruits made of water, agar, and blackberry [Rubus spec. (Rosaceae)] or guava [Psidium guajava L. (Myrtaceae)] pulp for 48 and 72 h. We also studied adult flies exposed for 72 h to essential oil of lemongrass [Cymbopogon citratus (DC) Stapf, Poaceae] and adult flies from larvae exposed to the oil. Control females were naive with respect to these experimental substrates. Prior experience with blackberry‐based artificial fruits resulted in an increase in the number of punctures and deposited eggs by A. fraterculus, and memory lasted for up to 72 h. On the other hand, fly behavior was independent of exposure to guava‐based substrate. Prior exposure of 1‐ or 15‐day‐old females to artificial substrate with lemongrass oil modified innate substrate selection behavior. The scent of lemongrass oil during the larval stage modified innate oviposition responses of adult A. fraterculus. The study shows that A. fraterculus females are able to learn and retain information through chemical stimuli released by both host (blackberry and guava) and non‐host (lemongrass) species, and they can use olfactory memory obtained during the larval stage to select oviposition sites.